1999
DOI: 10.1144/0051125
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and risk management in a small subsea-tieback: Arkwright Field, Central North Sea, UK

Abstract: Arkwright is a 50 × 106BBL oil field located within a single Forties Sandstone Member turbidite ‘channel’ system. Arkwright was discovered in 1990 and developed in 1996. Earlier start-up was precluded by reservoir risk and lack of export pipeline capacity. Reservoir definition improved after acquiring a 3D survey and applying imaging and attribute studies. This, combined with subsurface analogue, core, and carbon, oxygen and strontium isotopic studies, improved understanding of reservoir architecture and conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Earlier Sele and Lista formation maps (e.g. Kulpecz & Van Geuns 1990;Mudge & Bujak 1996a;Kantorowicz et al 1999;Ahmadi et al 2003;Hempton et al 2005;Kilhams et al 2012) show that these submarine fans are highly confined by the relict topography of the Central Graben rift structure. As such, the sandstone units predominantly comprise axial fans that thin from NW to SE (and on to the graben margins).…”
Section: Characterization Of the Maureen Lista And Sele Interval Sanmentioning
confidence: 93%
“…Earlier Sele and Lista formation maps (e.g. Kulpecz & Van Geuns 1990;Mudge & Bujak 1996a;Kantorowicz et al 1999;Ahmadi et al 2003;Hempton et al 2005;Kilhams et al 2012) show that these submarine fans are highly confined by the relict topography of the Central Graben rift structure. As such, the sandstone units predominantly comprise axial fans that thin from NW to SE (and on to the graben margins).…”
Section: Characterization Of the Maureen Lista And Sele Interval Sanmentioning
confidence: 93%
“…Studies of the Sele Formation (mainly based on regional three-dimensional seismic data) have concluded that there are two main sediment routes into the Central Graben: an along-graben axial system trending roughly NW to SE, and a crosscutting lateral system trending approximately west to east (Figs 3 & 4;Morton 1987;Kulpecz & Van Geuns 1990;Den Hartog Jager et al 1993;Kantorowicz et al 1999;Jennette et al 2000;Hempton et al 2005;Davis et al 2009). The lateral units may also be sourced from at least three discrete sources along the western margin of the Central Graben, allowing for the development of localized Bittern and Gannet Field sandstones within the S2 and S3 units ( Fig.…”
Section: Palaeogene Stratigraphy Of the North Seamentioning
confidence: 99%
“…3; Hempton et al 2005). The largest lateral system enters the basin within the Guillemot/Gannet Field area (Kantorowicz et al 1999), but there is some ambiguity as to how far east the related flows travelled. Hempton et al (2005), for example, used regional seismic isochron mapping ( Fig.…”
Section: Palaeogene Stratigraphy Of the North Seamentioning
confidence: 99%
“…However, with the widespread use of seismic attribute mapping, individual channel complexes can now be mapped with confidence and exploited ( Fig. 43; To date, production has occurred in the Andrew (Jolley 2003), Arbroath (Crawford et al 1991), Arkwright (Kantorowicz et al 1999;Hogg 2003), Balmoral Gambero & Currie 2003), Banff , Bladon, Blair, Blenheim (Dickinson et al 2001), Brae West, Crawford, Curlew (Eneyok et al (Wills 1991) and Brimmond (Carman & Young 1981;Carter & Heale 2003), Gannet B, C and D (Armstrong et al 1987), Glamis , Joanne, Lomond, MacCulloch (Gunn et al 2003), Machar (Foster & Rattey 1993), Maureen (Cutts 1991;Chandler & Dickson 2003a), Moira (Chandler & Dickson 2003b), Monan, Montrose (Crawford et al 1991 : Hogg op. cir.…”
Section: P a L A E O G E N Ementioning
confidence: 99%